2021
DOI: 10.7717/peerj.12437
|View full text |Cite
|
Sign up to set email alerts
|

First characterization of the probiotic potential of lactic acid bacteria isolated from Costa Rican pineapple silages

Abstract: Background Agro-industrial waste from tropical environments could be an important source of lactic acid bacteria (LAB) with probiotic potential. Methods Twelve LAB isolates were isolated from pineapple silages. The species identification was carried out considering 16S rRNA and pheS genes. Experiments to evaluate the probiotic potential of the isolates included survival under simulated gastrointestinal environment, in vitro antagonistic act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 69 publications
1
2
0
Order By: Relevance
“…Van D (glycopeptide class), cfr , optr A, and poxt A (oxazolidinone) were majorly discovered from smoked and environmental samples (surface swabs) with the following percentage values: 6.67% (95% CI: 2.21–11.13%) and 16.67% (95% CI: 10.0–23.34%), respectively. These genetic determinants were not observed in the 2008 studies but resulted in agreement with ones reported by another recent investigation [ 64 ] that interpreted these patterns due to the environmental pollution and to the consistent harboring in commensal bacteria as “ environmental reservoirs ”.…”
Section: Discussionsupporting
confidence: 89%
“…Van D (glycopeptide class), cfr , optr A, and poxt A (oxazolidinone) were majorly discovered from smoked and environmental samples (surface swabs) with the following percentage values: 6.67% (95% CI: 2.21–11.13%) and 16.67% (95% CI: 10.0–23.34%), respectively. These genetic determinants were not observed in the 2008 studies but resulted in agreement with ones reported by another recent investigation [ 64 ] that interpreted these patterns due to the environmental pollution and to the consistent harboring in commensal bacteria as “ environmental reservoirs ”.…”
Section: Discussionsupporting
confidence: 89%
“…The molecular analysis of the strains F, G and H allowed them to be classi ed as members of the genus Lentilactobacillus. In recent years, strains with probiotic potential that were identi ed within the genus Lentilactobacillus have been isolated and from vegetable and fermented food sources (Carasi et al, 2022;Ebrahimi et al, 2017;Wu et al, 2021). The genus Lentilactobacillus is mainly represented by Gram-positive, rod-shaped, catalase negative, heterofermentative strains, that mostly grow at 15°C and some also grow at 45°C.…”
Section: Discussionmentioning
confidence: 99%
“…Weissella and Periweissella species may play a role in the fermentation process of products both intended for human and animal consumption. They have been described as components of the fermentative microbiota of crop silages intended as animal feed (Otoni et al, 2018 ; Dong et al, 2020 ; Wang et al, 2020a ; Wen Fang Wu Wu et al, 2021 ), where Weissella spp. may be generally involved in early stages of fermentation (0–7 days) or even remain relatively stable during the subsequent stages of the process (Wang et al, 2020a ).…”
Section: An Update On the Ecology Of Weissella And...mentioning
confidence: 99%